Non-corrosive, low-toxicity gel-based microbattery from organic and organometallic molecules. Issue 43 (23rd October 2019) - Crespilho, Frank N.; Sedenho, Graziela C.; De Porcellinis, Diana; Kerr, Emily; Granados-Focil, Sergio; Gordon, Roy G.; Aziz, Michael J.
Abstract : The combination of natural hydrogel agarose and redox-active organic and organometallic molecules provides a non-corrosive, non-flammable and low-toxicity microbattery. Abstract : Microbatteries with safe, non-corrosive electrolyte chemistries can have an immediate positive impact on modern life applications, such as ingestible electronic pills and system-on-chip bioelectronics. Here a safe, non-corrosive and non-flammable microbattery is reported. A natural agarose hydrogel is the electrolyte-supporting matrix, and organic and organometallic molecules are the redox-active species. This device can safely meet the needs of ingestible medical microdevices as a primary battery. Additionally, this redox gel system can be used as a secondary battery for on-chip electronics applications, potentially enabling safe and cost-effective small-scale energy storage.